A Novel Cerium(IV)‐Based Metal‐Organic Framework for CO2 Chemical Fixation and Photocatalytic Overall Water Splitting. Issue 1 (6th December 2021) - Gu, Jia‐Xin; Chen, Hao; Ren, Yu; Gu, Zhi‐Gang; Li, Guangli; Xu, Wen‐Jie; Yang, Xin‐Yu; Wen, Jian‐Xin; Wu, Jing‐Tao; Jin, Hong‐Guang
Abstract: Cerium (IV)‐based metal‐organic frameworks (MOFs) are highly desirable due to their unique potential in fields such as redox catalysis and photocatalysis. However, due to the high reduction potential of Ce IV species in solution, it is still a great challenge to synthesize Ce IV ‐MOFs with novel structures, which are extremely dominated by the hexanuclear Ce−O cluster inorganic building units (IBUs). Herein, a Ce−O IBU chain containing Ce IV ‐MOF, CSUST‐3 (CSUST: Changsha University of Science and Technology), was successfully prepared using the kinetic stabilization study of UiO‐66(Ce)‐NDC (H2 NDC=2, 6‐naphthalenedicarboxylic acid). Furthermore, owing to the superior redox activity, Lewis acidity and semiconductor‐like behavior owing to Ce 4+, activated CSUST‐3 was demonstrated to be an excellent catalyst for CO2 chemical fixation. One‐pot synthesis of styrene carbonate from styrene and CO2 was achieved under mild conditions (1 atm CO2, 80 °C, and solvent free). Moreover, activated CSUST‐3 was shown to be a remarkable co‐catalyst‐free photocatalyst for overall water splitting (OWS), rendering 59 μmol g −1  h −1 of H2 and 22 μmol g −1  h −1 of O2 under simulated sunlight irradiation (Na2 S‐Na2 SO3 as sacrificial agent). Abstract : I Ce Now : A Ce IV ‐MOF with Ce−O chains as inorganic building units was successfully synthesized guided by the kinetic stabilization study of UiO‐66(Ce)‐NDC (H2 NDC=2, 6‐naphthalenedicarboxylic acid). Due to the superior redox activity, Lewis acidity and semiconductor‐like behavior owing to Ce 4+, activated CSUST‐3 (3 (CSUST: Changsha University of Science and Technology) was shown as an excellent catalyst for CO2 chemical fixation as well as a remarkable co‐catalyst‐free photocatalyst for overall water splitting.